An action research study on a process-genre approach to teaching IELTS writing task 2 to non-English major students at band 4.5-5.5 in a Vietnamese university setting - Trần, Thị Thơ (2016)
This research tries to seek the possibilities to apply process-genre approach in teaching writing skills to non-English major students in IELTS preparation courses. While each approach has its own upsides anddownsides in teaching application, the more effective one for writing needs is to incorporate the insights of these approaches (Badger & White, 2000). Also, this research aims to unpack the factors that effect students’ writing performance